Molybdenum disulfide nanosheet decorated with silver nanoparticles for selective detection of dopamine - Sookhakian, Mehran; Basirun, Wan Jefrey; Goh, Boon Tong; Woi, Pei Meng; Alias, Yatimah (Elsevier, 2019)
A metal-inorganic composite, comprises of silver-molybdenum disulfide nanosheets (Ag@MoS2) was synthesized at low temperature. The Ag@MoS2 composite was drop-casted onto a glassy carbon electrode (GCE) for a highly selective dopamine (DA) detection in the presence of interfering compounds such as uric acid (UA) and ascorbic acid (AA). The physicochemical analysis of the nanosheets was carried out with X-ray diffraction, transmission electron microscopy and X-ray photoelectron spectroscopy. The as-prepared Ag@MoS2-modified GCE displayed excellent electrocatalytic activity toward DA oxidation, with a 0.2 μM detection limit at a signal-to-noise ratio of 3 and an extensive linear detection range from 1 μM to 500 μM (R2 = 0.9983). The fabricated non-enzymatic electrochemical sensor demonstrated superior selectivity and stability for the detection of DA with the removal of AA and UA interfering compounds.